(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Terminalia chebula, Terminalia bellirica, Phyllanthus emblica and their formulations are used as a phytotherapeutic medicine for hepatic diseases. In the present study the effect of methanolic extract of herbal powder was administered against Imidacloprid in Albino Wistar Rats. Single dose of herbal (500 mg/kg/b.w) was given orally for 28 days to Imidacloprid toxicity exposed to rats. They were observed each hour and each day for 28 days for any changes in behavioural activity loss of ability to move, cramping, lethargy, muscle weakness, convulsion, irritation of the eye, excess salivation, change in gait. Clinical observations body weight, organ weight, biochemical analysis and histopathological examination were carried out. Administration of Imidacloprid, produced liver degeneration such as cytoplasmic vacuolation, mild vacuolar degeneration, mild hepatic damage in low dose (40 mg/kg b.w) and appearance of blood streaks, hepatic damage and severe vacuolar degenerations were observed in high dose of induction (80 mg/kg b.w). Animals were treated with the phytotherapeutic products of Terminalia chebula, Terminalia bellirica, Phyllanthus emblica and their formulations. Triphala extract was possessed more hepatoprotective activity, while comparing the four samples which was proved experimentally.